2018
DOI: 10.1021/acs.inorgchem.8b02973
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentally Different Distance Dependences of Electron-Transfer Rates for Low and High Driving Forces

Abstract: The distance dependences of electron transfer rates (k ET) in three homologous series of donor-bridge-acceptor compounds with reaction free energies (G ET 0) of ca.-1.2,-1.6, and-2.0 eV for thermal charge recombination after initial photoinduced charge-separation were studied by transient absorption spectroscopy. In the series with low driving-force, the distance dependence is normal and k ET decreases upon donoracceptor distance (r DA) elongation. In the two series with higher driving-forces, k ET increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…A comparison with CSS energies of other triads revealed that the stored energy typically amounts to about 1.5 eV upon visible light excitation,912,36 and in two recent CSS studies stored energies between 1.7 and 1.8 eV were declared as highly energetic 4,5. Recently, we reported on the distance dependence of thermal charge recombination in the compounds from Scheme 1a in comparison to two series of other molecular triads 16. The unusually high CSS energy of the two specific triads in Scheme 1a prompted us to perform a complete quantitative photophysical investigation including new multi-photon excitation studies, geared at understanding light-induced charge recombination.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A comparison with CSS energies of other triads revealed that the stored energy typically amounts to about 1.5 eV upon visible light excitation,912,36 and in two recent CSS studies stored energies between 1.7 and 1.8 eV were declared as highly energetic 4,5. Recently, we reported on the distance dependence of thermal charge recombination in the compounds from Scheme 1a in comparison to two series of other molecular triads 16. The unusually high CSS energy of the two specific triads in Scheme 1a prompted us to perform a complete quantitative photophysical investigation including new multi-photon excitation studies, geared at understanding light-induced charge recombination.…”
Section: Introductionmentioning
confidence: 92%
“…Encouraged by the efficiency of natural photosynthesis,1 numerous research groups have focused on mimicking its key steps. In particular, a great many studies explored molecular donor–acceptor compounds,227 in which the primary photoinduced charge separation was frequently enabled by a covalently linked photosensitizer 5,6,1016,19,24. Optimizing the primary charge separation is without any doubt one basic requirement for the realization of much more complex artificial systems allowing solar fuel production through multiphoton-driven charge accumulation 2831.…”
Section: Introductionmentioning
confidence: 99%
“…A key element in PSII is a tyrosine-histidine pair that mediates electron transfer between the P680 primary donor and the manganese-based OEC (18)(19)(20)(21)(22). Synthetic mimics for the biological relay have been investigated previously in molecular dyads and triads for water splitting electrodes (14,(23)(24)(25)(26):…”
mentioning
confidence: 99%
“…2b has a lifetime of 1.9 ms in de-aerated pyridine-pyridinium buffer at room temperature, and this is very similar to the typical lifetimes of classic charge-separated states in comparable molecular triads under similar conditions. [47][48][49][50][51] Thus, the fact that PCET is involved at both the donor and the acceptor unit has little influence on the kinetic stability of the photoproduct, but it could make accumulation of redox equivalents after secondary photoexcitation more feasible as noted above. However, even when the build-up of charges is avoided, many challenges remain for productive multi-electron transfer, as discussed in the following.…”
Section: From Separating Electrons and Holes To Separating Redox Equimentioning
confidence: 99%
“…3.5 eV of energy, whilst common donorsensitizer-acceptor triads typically store only 1.4-2.0 eV. 47,49,51,70 There were only two prior studies of charge-separated states in which two electrons are reversibly accumulated on a single acceptor of a purely molecular system, and in both cases the lifetime of that state was shorter than 10 ns. 64,65 In presence of 0.2 M p-toluenesulfonic acid (TsOH), AQ 2À is protonated and the hydroquinone AQH 2 forms, leading to an overall photoproduct comprised of two TAA + units and one AQH 2 with a lifetime of 4.7 ms in CH 3 CN at room temperature.…”
Section: Pcmet In Molecular Donorbridge-acceptor Compoundsmentioning
confidence: 99%